2016
DOI: 10.1002/2015gc006034
|View full text |Cite
|
Sign up to set email alerts
|

Composition, geometry, and emplacement dynamics of a large volcanic island landslide offshore Martinique: From volcano flank‐collapse to seafloor sediment failure?

Abstract: +33 (0) 1 83 95 76 38Key points: -First drilling into submarine landslide deposits offshore volcanic island -Large (300 km 3 ) submarine landslide deposit offshore Martinique comprises mainly deformed seafloor sediment, in a single frontally emergent morphology Research ArticleGeochemistry, Geophysics, Geosystems DOI 10.1002/2015GC006034This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 52 publications
9
74
0
Order By: Relevance
“…A similar two-fold nature of volcanic flank-collapse depositshummocky debris avalanche deposits accompanied by acoustically transparent to seismically chaotic deposits with a comparatively smooth upper surfacehas also been reported for flank-collapses at other locations, including in the Lesser Antilles (Watt et al, 2012a, b;Le Friant et al 2015;Brunet et al 2016); at La Réunion (Indian Ocean; Lebas et al 2018); and at Ritter Island (Papua New Guinea; Karstens et al 2019;Watt et al 2019). Drilled cores retrieved during IODP Expedition 340 in the Lesser Antilles indicated that widespread, seismically chaotic deposits (interpreted as equivalent to our MTD-B) primarily consist of hemipelagic mud interbedded with a combination of tephra, volcaniclastic layers, or bioclastic turbiditic deposits, which have undergone varying degrees of deformation (Le Friant et al 2015;Brunet et al 2016). To explain these findings, Le Friant et al (2015) proposed a failure model where the loading of seafloor sediment by volcanic debris avalanche deposits triggered sediment destabilization…”
Section: The Two-fold Nature Of Fogo's Monte Amarelo Flank-collapsesupporting
confidence: 62%
See 1 more Smart Citation
“…A similar two-fold nature of volcanic flank-collapse depositshummocky debris avalanche deposits accompanied by acoustically transparent to seismically chaotic deposits with a comparatively smooth upper surfacehas also been reported for flank-collapses at other locations, including in the Lesser Antilles (Watt et al, 2012a, b;Le Friant et al 2015;Brunet et al 2016); at La Réunion (Indian Ocean; Lebas et al 2018); and at Ritter Island (Papua New Guinea; Karstens et al 2019;Watt et al 2019). Drilled cores retrieved during IODP Expedition 340 in the Lesser Antilles indicated that widespread, seismically chaotic deposits (interpreted as equivalent to our MTD-B) primarily consist of hemipelagic mud interbedded with a combination of tephra, volcaniclastic layers, or bioclastic turbiditic deposits, which have undergone varying degrees of deformation (Le Friant et al 2015;Brunet et al 2016). To explain these findings, Le Friant et al (2015) proposed a failure model where the loading of seafloor sediment by volcanic debris avalanche deposits triggered sediment destabilization…”
Section: The Two-fold Nature Of Fogo's Monte Amarelo Flank-collapsesupporting
confidence: 62%
“…Many such events have volumes in the order of tens to hundreds of cubic kilometres, e.g. at Nisyros Volcano in the Aegean Sea (Tibaldi et al 2008;Livanos et al 2013); in the Lesser Antilles Arc (Lebas et al 2011;Le Friant et al 2015;Brunet et al 2016); in the Canary Islands (Krastel et al 2001;Masson et al 2002;León et al 2017); and in the Cape Verde Islands (Masson et al 2008). However, even comparatively small-volume volcanic flank-collapses, such as the 0.22-0.3 km 3 Anak Krakatau flank-collapse in December 2018 (Grilli et al 2019), may result in catastrophic tsunamis.…”
Section: Introductionmentioning
confidence: 99%
“…The Integrated Ocean Drilling Program Expedition 340 carried out offshore the Lesser Antilles provided for the first time evidence for the composition and origin of such chaotic units offshore Montserrat and Martinique Islands. The seismically chaotic deposits were successfully drilled and exclusively recovered seafloor sediment (including mud, tephra layers, and turbidites), revealing a complete lack of volcanic debris avalanche deposits (Brunet et al, ; Le Friant et al, ). Le Friant et al () interpreted these “seismically chaotic facies” deposits as resulting from widespread deformation of pre‐existing sediment on the abyssal plain, triggered by the emplacement of debris avalanche deposits on the edifice flank.…”
Section: Discussionmentioning
confidence: 99%
“…volcanic flanks (Lafuerza et al 2014;Hornbach et al 2015;Brunet et al 2016); passive margins (Sawyer et al 2009); glacial margins (Laberg & Camerlenghi 2008). With the example provided from the GoL, we further support the evidence that lithological heterogeneity within the sediment successions is a key to localisation of seafloor instability.…”
Section: Sedimentological Geotechnical and Geophysical Properties Ofmentioning
confidence: 99%